Tinjauan Sejarah Mekanisme Pasar Dalam Islam - Nur Syamsu (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2016)
The paper attempts to analysis the concept of market mechanism in Islamic view as developed by the Muslim scholars. The ideas of Muslim scholars are at large remained unexplored who had offered rather detailed and sophisticated discourse on market and pricing mechanism. Our study is confined to the ideas of following representative personalities such as Abu Yusuf, al-Ghazali, Ibn Taimiyah and Ibn Khaldun. The paper concludes with the note that considerable ideas on the market and pricing mechanism were found with the Muslim scholars long before the mid-eighteenth century, and that the views of Islamic writers were far detailed and clear. This requires reconsideration on Schumpeter‟s statement about mechanism of pricing that nothing worth mentioning existed before the middle of eighteenth century. Especially the contribution of the Arab-Islamic scholars to economic thought be rehabilitated in the science of economics for the sake of doctrinal continuity as well as objectivity.